The Self-Concept Construction of Tattoo Users - Heru Nugroho (Metakom, 2018)
Basically tattoo which is on the body of tattoo users has their own meaning or a symbol that represents their feelings. The purpose of this study to explain and analyze the construction of self-concept tattoo users in Bandar Lampung. The theory used in this research was the theory of symbolic interaction using constructivism approach. This research used qualitative research type with data collection technique through observation and in-depth interview with informant that is six tattoo users in Bin Ban Tattoo Bandar Lampung. The results of this study indicated that the tattoo user has a positive self concept, positive, and negative, and has three important components on the concept itself namely mind, self, and society. Positive self-concept occurs where the environment supports it using tattoos and tattoo users also feel happy and comfortable with the tattoos that use. The positive concept also occurs where the environment does not support it using tattoos but tattoo users still feel happy and do not care about the environmental response. While the negative self-concept occurs where the surrounding environment does not support it and tattoo users also do not like and uncomfortable with the existing tattoo in his body. Keywords: symbolic interaction, construction, constructivism, self-concept, and tattoo